C.H.A.N.G.E? : clinicians' health actions naturally generate effectiveness? : the development of a model of a model for a clinically integrated system for patient care management : a thesis presented in partial fulfilment of the requirements for the degree of Master of the Arts in Nursing at Massey University - Fogarty, Anne Marie (Massey University, 2000)
In 1997, Auckland Healthcare established the A+ Network Centre for Best Patient Outcomes. The development of this Centre was an initiative designed to support clinicians in their mission to achieve excellence of care for patients. This goal has led to a fundamental rethinking of how we currently manage patient care. The Centre's inability to find a system that could meet the needs of both patients and clinicians in improving patient outcomes has led to the development of our own generic clinically integrated system (CIS) model. The CIS model links three specialised ideologies that have previously been used in health care but in isolation from one another. The concepts of evidence based practice, clinical redesign, and patient outcomes are brought together to form a single interdisciplinary framework for managing patient care. An integral part of this model is the use of a participatory action research approach to achieve this aim. This thesis begins with a description of the theoretical underpinnings that have influenced the developmental strategy for establishing a generic CIS model. The discussion focuses on the development of the Centre, the contribution that literature has made to the development of a CIS model, and how the Centre members have used these findings to design a generic CIS model. Later in the thesis there is a discussion of the development of a CIS model within an Orthopaedic Service, which provides the opportunity to illustrate, via the use of a case study, the practical applicability of this model. While this thesis primarily focuses on the case study, which entails the development of the CIS model for patients with a fractured ankle, the implications of this project have wider ramifications. Our prior participatory experiences with the development of the CIS model for patients with a fractured neck of femur would impact on some of the decisions made in this case study. In particular, the evaluation findings from the implementation phase of the fractured neck of femur project highlighted the need for a more sophisticated information infrastructure to support the intentions of a CIS model. The intended outcome of the establishment of a CIS model for patients with fractured ankles consequently expanded to incorporate a CIS model for patients with fractured neck of femurs using a generic computerised CIS model template to achieve these aims. The development of a computerised generic CIS model has the potential to revolutionise the way in which we care for patients. The capacity to concurrently track and manage patient outcomes has moved from evaluating the effectiveness of care from an individual patient's perspective to incorporating groups of patients. Central to this process is the establishment of conditions that will enhance the participatory input from all interested parties. In particular, this has meant introducing new avenues for patient participation. However, before this goal could be achieved, our first priority as clinicians was to accept the need for change and introduce the concepts of evidence based practice, clinical redesign and patient outcomes via a process which can embed these principles into our daily practice.
Keywords: Medical care quality; Health services administration; Patient outcomes